Full-Scale Laboratory Test of Cutting Large-Diameter Piles Directly by Shield Cutterhead - Yuqing Wang; Xinyu Wang; Yangyang Xiong; Zhuangzhi Yang; Jie Zhang (Advances in Civil Engineering)
Based on the TBM tunnel of Red Line of Tel Aviv in Israel, this paper carried out laboratory tests of shield cutting concrete and reinforced concrete piles and investigated cutting performance of cutter, failure model of rebars, length of damaged rebars, and cutter vibration. The results indicate that under the condition of low tunneling speed and rotating speed, vibration of the cutterhead is small, and vibration of the center cutterhead is more obvious in the radial direction of the cutterhead. Cross sections of broken rebars mainly consist of shear section, tensile-shear section, tensile-compressive section, and bending section. Considering the tunnel status, it is recommended to adopt excavation speed of 3∼5 mm/min, and rotating speed of 1.0∼1.3 r/min. While cutting RC piles, the principle of “low excavation speed, high rotating speed, and less disturbance” is recommended. Cutting with disc cutters is efficient and the torque of which is stable but the length of the rebars got from cutting varies a lot. It is recommended that majorities of the cutters shall be disc cutters and supplemented with drag bits and tear cutters.